Pengaruh Resilience at Work terhadap Work Engagement pada Dokter Hewan - Bunga Safa Genita; Dinda Dwarawati (UNISBA Press, 2023)
Abstract. Work engagement is a positive individual state of mind that can express itself well in terms of physical, psychological, and affective into the work. Resilience at work is an ability of compromising with oneself in managing and adapting the stressor that can be developed to balance the work tension in workplace. Veterinarians are one of the professions in the health sector that have high job demands related to work stress and fatigue so that it has an impact on work performance. This research uses a non-experimental quantitative research method with the aim of analyzing the effect of resilience at work on workengagement in veterinarians. The participants included of 94 veterinarians who are members of PDHI West Java 1. Data collection was carried out using the Resilience At Work (RAW) Scale from Malik and Garg (2018) which was adapted by researchers and the Ultrecht Work Engagement Scale-17 (UWES- 17) by Schaufeli & Bakker (2004). The results showed that there was a significant effect of resilience at work on work engagement of 60.7%. The results of multiple regression show that the aspect of building social connection has the highest significant effect on work engagement.Abstrak. Work engagement merupakan sebuah keadaan pikiran individu yang positif sehingga dapat mengekspresikan dirinya dengan baik dari segi fisik, psikis, dan afektif ke dalam pekerjaannya. Resilience at work merupakan kemampuan berkompromi dengan diri sendiri dalam mengelola dan beradaptasi dengan sumber stres yang bisa dikembangkan untuk mengimbangi ketegangan kerja di tempat kerja. Dokter hewan merupakan salah satu profesi di bidang kesehatan yang memiliki tuntutan pekerjaan tinggi yang berkaitan dengan stres kerja dan kelelahan sehingga berdampak pada perfroma kerja. Penelitian menggunakanmetode penelitian kuantitatif yang bersifat kausalitas non-eksperimental dengan tujuan untuk menganalisis pengaruh resilience at work terhadap work engagement pada dokter hewan. Partisipan terdiri dari 94 orang dokter hewan anggota PDHI Jawa Barat 1. Pengumpulan data dilakukan dengan menggunakan alat ukur Resilience At Work (RAW) Scale dari Malik dan Garg (2018) yang telah diadaptasi peneliti dan Ultrecht Work Engagement Scale-17 (UWES-17) yang dirancang oleh Schaufeli & Bakker (2004). Hasil penelitian menunjukkan adanya pengaruh signifikan resilience at work terhadap work engagement sebesar 60,7%. Hasil multiple regression menunjukkan bahwa aspek building social connection memberikan pengaruh signifikan tertinggi terhadap work engagement.